Typification of the Lacaita’s name Senecio stabianus (Asteraceae), basionym of the Italian endemic Senecio ovatus subsp. stabianus - Stinca, Adriano (Phytotaxa, 2022)
In order to investigate the nomenclature of taxa described by Charles Carmichael Lacaita, in this paper the name Senecio stabianus is lectotypified based on a specimen mounted on two sheets, which constitute a single gathering, traced in BM. Currently, this Italian endemic taxon is treated as a subspecies of S. ovatus and listed in the IUCN Red List.